Criteria of fitness for anaesthesia in patients with chronic obstructive lung disease. Issue 5985 (20th September 1975) - Milledge, J S; Nunn, J F
Abstract : Twelve patients with severe chronic obstructive lung disease undergoing 15 operations were assessed with preoperative lung function tests and blood gas estimations. Their operative and postoperative course was followed. There were no deaths or serious complications. Patients fell into three groups: those with low respiratory capacity but normal blood gases, who required no special respiratory treatment apart from physiotherapy and antibiotics; those with hypoxaemia but normal arterial carbon dioxide pressure, who needed more prolonged oxygen treatment after operation; and those with hypoxaemia and hypercapnia, who needed postoperative ventilatory support. While forced expiratory volume in one second (FEV) is a good screening test in preoperative assessment it should be supplemented by arterial blood gas estimations in patients with an FEV of less than 1 litre.